Performance analysis of generalized processor sharing based on fractal leaky bucket regulators - CHEN Zhi-gang; ZHANG Lian-ming; DENG Xiao-heng; ZHAO Ming (Tongxin xuebao)
In order to analyze the effect of self-similar traffic on the generalized processor sharing（GPS）,the relationship was explored between the performance of a GPS system and the parameter of self-similar traffic.The self-similar traffic getting into the GPS system was regulated using the envelope curve of the fractal leaky bucket（FLB）.The upper bounds on queue length and delay of the GPS system with self-similar traffic input was derived.Numerical simulations demonstrate that the performance model of a GPS system based on fractal leaky bucket regulators is suited for the self-similar traffic.